Uso de caolín para el manejo de insectos plaga en el cultivo de tomate (Solanum lycopersicum) - Vera Saltos, Dayann Andrea (2023)
One of the main limitations that affect the cultivation of tomato (Solanum lycopersicum) are pest insects which cause significant economic losses. The main form of pest control is the use of highly toxic pesticides. Alternative pest control measures are required. The objective of the research was to evaluate the effect of kaolin for the management of pest insects in tomato cultivation. The research was carried out on the "La María" campus (State Technical University of Quevedo). The treatments used were: 20 g/L kaolin (T1), 40 g/L kaolin (T2), 60 g/L kaolin (T3), water (T4) and insecticide (T5). The evaluated variables were subjected to the analysis of variance and later to the 95% Tukey test for comparison of means when required. Five pest species were identified in the tomato crop (Bemisia tabaci (808), Prodiplosis longifila (219), Euchistus sp. (134), Myzus persicae (112), Manduca sexta (24)). The highest values of stem diameter, plant height and yield were obtained in the treatments in which kaolin was used (T3 =1,24 mm; T2=105,73 cm and T1 =8958,71 kg/ha). Finally, it was possible to verify that there is repellency of B. tabaci to plants exposed to kaolin during 1h, 6h, 12h, and 24h of exposure (P<0.001). Kaolin allows pest control, improves the agronomic and productive characteristics of the tomato crop, therefore; its use should be considered within integrated pest management programs. Keywords: Control, bioinsecticide, repellency, white fly.